The BRCA1 Methylation and PD-L1 Expression in Sporadic Ovarian Cancer. Issue 8 (October 2018) - Zhu, Xinxin; Zhao, Ling; Lang, Jinghe
Abstract : Objective: This study aimed to assess the relationship between BRCA1 gene methylation, PD-L1 protein expression, and the clinicopathologic features of sporadic ovarian cancer (OC). Methods: Bisulfite pyrosequencing and immunohistochemistry were used to detect BRCA1 gene methylation and PD-L1 protein expression, respectively, in tumor tissues from 112 patients with sporadic OC. Their levels were analyzed against clinicopathologic characteristics and prognosis using standard statistical methods. Results: Twenty percent (22/112) of the OC cases exhibited BRCA1 gene hypermethylation. The frequency of BRCA1 hypermethylation was significantly higher in serous OC (25%) than in nonserous OC (8%; P < 0.05). No significant correlations were discovered between BRCA1 hypermethylation and age, menstrual status, tumor location, stage, lymph node metastasis, and prognosis ( P > 0.05). Among the 112 OC cases, 59% (66/112) cases were positive for PD-L1 protein expression. No significant difference existed between PD-L1 expression and age, menstrual status, histological type, tumor location, stage, lymph node metastasis, and prognosis ( P > 0.05). Moreover, no correlation existed between BRCA1 methylation and PD-L1 expression ( P > 0.05, r = 0.002). Conclusions: This is the first study linking BRCA1 hypermethylation variability to PD-L1 protein expression and the clinicopathologic features of OC. The data demonstrated that an epigenetic alteration of BRCA1 was closely associated with serous OC. The expression of PD-L1 was unrelated to the clinicopathologic features or BRCA1 hypermethylation in sporadic OC.